(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Myasthenia gravis (MG) is an autoimmune neuromuscular junction (NMJ) disorder characterized by weakness and fatigability of skeletal muscles. Myasthenia gravis has prevalence as high 200 in 100,000. It affects individuals in all age groups, but peak incidences occur in women in their twenties and thirties and in men in their fifties and sixties. Overall, women are affected more frequently than men, in a ratio of 3:2. It has bimodal age distribution. In MG, the fundamental defect is a decrease in the number of available AChRs at the postsynaptic muscle membrane. It presents with fluctuating skeletal muscle weakness and fatigue most commonly affecting the ocular muscles, although any muscle may be affected. In modern science treatment of Myasthenia gravis include anti-cholinesterase medications, glucocorticoids and other immunosuppressive agents. Long term use of steroid and immune modulator drugs has many adverse effects on other system of body. Ayurvedic therapies can give much more promising results. Comparison between myasthenia gravis and diseases explained in Ayurveda is difficult and exact correlation is not possible. But based on critical understanding of Vyadhighataka, a probable diagnosis can be made and treated accordingly. In this article, attempt is made to understand the pathogenesis of myasthenia gravis by considering the concepts of Dosha (vitiated Dosha), Dushya (vitiated Dushya), Aama, Agnimandya, and Srotovaigunya. For any disease pathology to begin, all components must be present. Pathogenesis of any disease will not occur without these elements.